When the whole is greater than the sum of its parts: towards a characterization of students’ mathematics discourse participation profiles: When the whole is greater than the sum of its parts: towards a characterization of students’ mathematics discourse participation profiles - Macchioni, Elena; Baccaglini-Frank, Anna (Educational studies in mathematics, 2025)
Many students are finishing secondary school without the essential mathematical skills needed to participate in social activities. Research in mathematics education has been investigating the phenomenon of persistent low achievement in mathematics learning from various perspectives, including cognitive, affective, and social ones. Each perspective captures a dimension but generally fails to elaborate sufficiently on its intertwining with the others, leading to fractures in the literature and to only partial insights into ways to enable students to engage with mathematics. Our work seeks to take a step in this direction, bridging the fracture between cognitive and non-cognitive perspectives and gaining insight into ways to improve the design of mathematics remediation activities, by synergistically combining a set of constructs from the Theory of Commognition to sketch out low-achieving secondary school students’ mathematics discourse participation profiles. Our analytic tool, together with a carefully designed interview, allows us to identify, within a student’s discourse, both the mathematizing (cognitive) and the identifying (non-cognitive) dimensions, as well as their interplay, thanks to a methodical inference process of the student’s metadiscursive rules. As an example, we identify the discursive profile of Elsa, a 10th-grade student manifesting very low achievement in mathematics.